2017
DOI: 10.25037/pancaran.v6i4.118
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Learning Syntax Model Using Open-Ended Problem Solving To Develop Students’ Creativity

Abstract: The focus of this research was to develop a syntax model forMathematics learning using open-ended problem solving that can develop students' creativity. The emphasis on creativity development was done since the curriculum and the experts also emphasize it. This can be understood since someone with high creativity can quickly make innovations or new breakthroughs. The design research used in this study followed Plomp's design research (2007), which consisted of: (1) preliminary research phase; (2) prototyping p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 2 publications
(2 reference statements)
1
7
0
7
Order By: Relevance
“…Several researchers confirmed that creative teachers could maximize the potential growth of students in terms of their knowledge, experiences, skills, and engagement in real-life tasks [18,26,27]. Further, Suastika [28] even emphasized that it is the duty of the Mathematics teachers to encourage students' creativity, and it is necessary for them to provide a conducive environment for the optimal development of such skill. Nonetheless, to prepare them in this significant role, investigation, and cultivation of mathematical creativity of future teachers is urgent and is gravely important.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers confirmed that creative teachers could maximize the potential growth of students in terms of their knowledge, experiences, skills, and engagement in real-life tasks [18,26,27]. Further, Suastika [28] even emphasized that it is the duty of the Mathematics teachers to encourage students' creativity, and it is necessary for them to provide a conducive environment for the optimal development of such skill. Nonetheless, to prepare them in this significant role, investigation, and cultivation of mathematical creativity of future teachers is urgent and is gravely important.…”
Section: Introductionmentioning
confidence: 99%
“…Sejalan dengan Sa'dijah (2013) bahwa pembelajaran matematika di sekolah berperan penting dalam menumbuhkan serta mengembangkan kemampuan berpikir logis dan kreatif siswa. Guru diperlukan untuk mengembangkan kreativitas siswa dalam pembelajaran matematika (Suastika, 2017). Perlu adanya pembiasaan yang konsisten dalam pembelajaran matematika untuk melatih dan mengembangkan kemampuan berpikir kreatif (Susilo, dkk., 2018).…”
unclassified
“…Judging from the differences in these steps, it can be seen that the ATI model at the grouping stage of students and the intensive treatment given to students has a high influence on improving students' mathematical creative thinking abilities (Syazali et al, 2019), since students can implement new ideas in a group and find various solutions from an issue. Besides there is room for an approach between the teacher and students by giving appropriate treatment to the aptitude of students as a result of learning mathematics in the classroom experiencing optimal improvement in results (Laurens et al 2017;Suastika, 2017;Sitorus & Masrayati 2016;Tohir et al 2018;Yew & Goh 2016;Lehmann, Goussios, & Seufert 2016;Pamungkas & Afriansyah 2017).…”
Section: Discussionmentioning
confidence: 99%